Insecticidal potential of defense metabolites from ocimum kilimandscharicum against helicoverpa armigera - Singh, Priyanka; Jayaramaiah, Ramesha H.; Sarate, Priya; Thulasiram, Hirekodathakallu V.; Kulkarni, Mahesh J.; Giri, Ashok P. (Plos One, 2014)
Genus Ocimum contains a reservoir of diverse secondary metabolites, which are known for their defense and medicinal value. However, the defense-related metabolites from this genus have not been studied in depth. To gain deeper insight into inducible defense metabolites, we examined the overall biochemical and metabolic changes in Ocimum kilimandscharicum that occurred in response to the feeding of Helicoverpa armigera larvae. Metabolic analysis revealed that the primary and secondary metabolism of local and systemic tissues in O. kilimandscharicum was severely affected following larval infestation. Moreover, levels of specific secondary metabolites like camphor, limonene and beta-caryophyllene (known to be involved in defense) significantly increased in leaves upon insect attack. Choice assays conducted by exposing H. armigera larvae on O. kilimandscharicum and tomato leaves, demonstrated that O. kilimandscharicum significantly deters larval feeding. Further, when larvae were fed on O. kilimandscharicum leaves, average body weight decreased and mortality the larvae increased. Larvae fed on artificial diet supplemented with O. kilimandscharicum leaf extract, camphor, limonene and beta-caryophyllene showed growth retardation, increased mortality rates and pupal deformities. Digestive enzymes of H. armigera - namely, amylase, protease and lipase- showed variable patterns after feeding on O. kilimandscharicum, which implies striving of the larvae to attain required nutrition for growth, development and metamorphosis. Evidently, selected metabolites from O. kilimandscharicum possess significant insecticidal activity.

Investigation of antiglycation activity of isoprenaline - Kolekar, Yogesh M.; Vannuruswamy, Garikapati; Bansode, Sneha B.; Santhakumari, B.; Thulasiram, Hirekodathakallu V.; Kulkarni, Mahesh J. (RSC Advances, 2015)
Advanced glycation end products (AGEs) are implicated in pathogenesis of diabetes and its complications. In this study, we report the ability of isoprenaline to inhibit the AGE modification of protein by fluorescence spectroscopy and western blotting. Isoprenaline was more effective in inhibiting AGE modification than aminoguanidine, a well known glycation inhibitor. Further, we show that isoprenaline inhibits at Amadori product formation during glycation reaction by various techniques such as MALDI-TOF-MS, LC-MS/MS, and fructosamine assay. Mass spectrometric analysis of the glycation reaction mixture incubated with isoprenaline suggested that it forms adducts with glucose and thus inhibits glycation. The finding of the additional property of isoprenaline of inhibiting glycation suggests that it is a potential candidate for drug repositioning for the treatment of diabetes and its complications, as it is an FDA approved drug.

Ion pairing in 1-butyl-3-methylpyridinium halide ionic liquids studied using NMR and DFT calculations - Swamy, Vincent P.; Thulasiram, Hirekodathakallu V.; Rastrelli, Federico; Saielli, Giacomo (Physical Chemistry Chemical Physics, 2018)
We present the H-1, C-13 and N-15 NMR chemical shifts of bulk ionic liquids based on 1-butyl-3-methylimidazolium (the cation also known as 1-butyl-3-picolinium) halides (Cl-, Br- and I-) and tribromide (Br-3(-)) salts. A characterization in solution of the analogous ICl2- and I-3(-) salts is also reported. A series of DFT calculations has been run to predict the features of the NMR spectra of the pure ILs based on a few selected supramolecular ionic aggregates. To test the effect of temperature, and vibrational and conformational motions, only for the chloride salt, we also run first-principles molecular dynamics simulations of the ion pair in the gas phase, using the ADMP scheme (Atom Centered Density Matrix Propagation molecular dynamics model). The aim of our investigation is to test whether a simple DFT based approach of ion-pairing in ionic liquids is capable of providing reliable results and under which conditions the protocol is robust. We obtained a very good agreement between the calculated and experimental spectra for the three halides, where the bulk structure of the ILs is dominated by H-bond interactions between the X- anion (X = Cl, Br and I) and the ortho protons of the pyridinium ring (a structural arrangement not too different from the solid-state structure of pyridinium halides). In contrast, when the H-bond is weak, as in the Br-3(-) case, a number of supramolecular arrangements exist in solution and the simple DFT calculations of a few selected cases cannot exhaustively explore the complete energy landscape. Moreover, the dynamic effects due to thermal motion, evaluated by ADMP MD simulations of the chloride salt, appear to be not very significant.